1982
DOI: 10.1128/aem.44.2.471-477.1982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Area and Flow Rate on Marine Bacterial Growth in Activated Carbon Columns

Abstract: The colonization of granular activated carbon columns by bacteria can have both beneficial and potentially detrimental consequences. Bacterial growth on the carbon surface can remove adsorbed organics and thus partially regenerate the carbon bed. However, growth can also increase the levels of bacteria in the column effluents, which can adversely affect downstream uses of the treated water. This study of a sand column and several activated carbon columns demonstrated that considerable marine bacterial growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Six devices (UA24, 28,29,30,32,38) were received with the tailstrings still attached to the device body while five devices (V5, UA18,34,43,64) had their tailstrings separated from the device body by intentional laboratory removal for culturing a section of the tailstring in the Fives-Taylor laboratory as described above. In the Robertson laboratory, each tailstring, except for UA64, was cut into sections of approximately 1 cm in length.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Six devices (UA24, 28,29,30,32,38) were received with the tailstrings still attached to the device body while five devices (V5, UA18,34,43,64) had their tailstrings separated from the device body by intentional laboratory removal for culturing a section of the tailstring in the Fives-Taylor laboratory as described above. In the Robertson laboratory, each tailstring, except for UA64, was cut into sections of approximately 1 cm in length.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Interest in biofilm formation has been driven by the importance of bacterial activity in many technological applications, together with a growing ability to exert control over surface properties. In particular, the ongoing effort to design antibacterial surfaces has served to identify a number of substratum surface characteristics that might influence bacterial attachment, including morphology, composition, roughness and porosity [9,10,[24][25][26][27][28][29]. According to one common scenario of biofilm formation, bacterial adhesion is initiated in surface irregularities that serve as microenvironments where bacteria are sheltered from unfavorable environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the best pore size for attachment should range between the smallest cell dimension and five times its largest dimension. Shimp and Pfaender [22] also reported that microbe-size crevices favor surface colonization.…”
Section: Introductionmentioning
confidence: 94%